2019
DOI: 10.3390/cancers11101585
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Demethylase LSD1/ΚDM1A Mediates Chemoresistance in Breast Cancer via Regulation of a Stem Cell Program

Abstract: Breast cancer is the leading cause of cancer death in the female population, despite advances in diagnosis and treatment. The highly heterogeneous nature of the disease represents a major obstacle to successful therapy and results in a significant number of patients developing drug resistance and, eventually, suffering from tumor relapse. Cancer stem cells (CSCs) are a small subset of tumor cells characterized by self-renewal, increased tumor-initiation capacity, and resistance to conventional therapies. As su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 67 publications
2
43
0
Order By: Relevance
“…Interestingly, combination treatment of mouse xenografts with the drug and an LSD1 inhibitor led to reduction of tumor volume [105]. Similar data on LSD1 regulation of b-CSCs and its therapeutic potential were also obtained by our group [106]. LSD1 knock-down and pharmacological inhibition impaired the stemness properties and significantly reduced the number of CD44 + -CD24 -CSCs in vitro.…”
Section: Lsd1 In Breast Cancer Stem Cellssupporting
confidence: 77%
See 3 more Smart Citations
“…Interestingly, combination treatment of mouse xenografts with the drug and an LSD1 inhibitor led to reduction of tumor volume [105]. Similar data on LSD1 regulation of b-CSCs and its therapeutic potential were also obtained by our group [106]. LSD1 knock-down and pharmacological inhibition impaired the stemness properties and significantly reduced the number of CD44 + -CD24 -CSCs in vitro.…”
Section: Lsd1 In Breast Cancer Stem Cellssupporting
confidence: 77%
“…More interestingly, by in vitro manipulation of the LSD1 levels, we showed that it conferred increased chemoresistance to breast cancer cells. Using a 3D tumorsphere system, we also demonstrated that combined administration of an LSD1 inhibitor (2-PCPA or GSK-LSD1) and a conventional drug (doxorubicin or paclitaxel) had a synergistic effect and led to a significant reduction in their number, while it targeted the CSC-subpopulation [106].…”
Section: Lsd1 In Breast Cancer Stem Cellsmentioning
confidence: 83%
See 2 more Smart Citations
“…The importance of LSD1 in differentiation suggests that dysregulation of LSD1 activity may alter pathways associated with stem-cell-like phenotypes (8). In support of this, overexpression of LSD1 has been shown to promote cell proliferation, migration, and invasion in a variety of human cancers (4,(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 92%